A Review on Deep Learning Based Sign Language Recognition Translation - Huang, Junkai (International Journal of Computer Science and Information Technology, 2024)
Hand posture is often referred to as gesture. It refers to the specific movements and postures that occur when a person utilizes his or her arms. It is one of the earliest and still widely used communication tools. In general, gestures are both dynamic and static. In the process of long-term social practice, gestures are given a variety of specific meanings, has a rich expressive power, the range of motion is extensive when the fingers, wrists, elbows, shoulders, and other joints of the hand are considered. The capacity for flexibility is considerable. Gestures have become a primary means of expression for humans, enabling the conveyance of emotions. In this context, body language occupies a pivotal role. Sign language is defined as the use of hand gestures with or without the use of facial expressions to convey meaning. The combination of hand gestures and facial expressions can be used to imitate images or to represent syllables, which together constitute a certain meaning or word. Sign language is a means of communication for individuals who are deaf or hard of hearing. It is an essential tool for communication, enabling them to express themselves and interact with others in a way that is accessible and understandable. This paper summarizes the deep learning based gesture recognition techniques in recent six years. In recent years, gesture recognition has been in the hot spot, and every year the articles on gesture recognition are constantly updated, so it is evident that a review of the research on gesture recognition is very necessary. This paper also compares and analyzes the existing gesture recognition methods and analyzes their advantages and disadvantages, and puts forward an outlook on the future development.